O Processamento da prosódia implícita na leitura silenciosa do português escrito por surdos congênitos profundos bilaterais bilíngues Libras/Português do município de Tomé-Açu-PA - SILVA, Rayse Rodrigues da (2024)
In this work, we mainly investigated the processing of implicit prosody in the silent reading of Portuguese written by bilateral profound congenitally deaf Libras/Portuguese bilinguals. Specifically, we analyze the processing of graphic prosodic marking in silent reading of written Portuguese by this audience. Additionally, we compared the comprehension of silent reading of written Portuguese with/without graphic prosodic marking performed by bilateral congenitally deaf Libras/Portuguese bilinguals. We adopted Fodor's (2002, apud Carvalho, 2016) “Implicit Prosody Hypothesis” that both syntactic and prosodic structures are computed during silent reading and; Cagliari's hypothesis (1989) in which punctuation marks function as prosodic markers in writing. We also applied a non-timed, offline, silent reading experiment. Our assumptions were that a) Libras/Portuguese bilingual deaf people would possess and perform the implicit prosody during silent reading of written Portuguese; b) graphic prosodic marking would facilitate the processing of silent reading of Portuguese written by deaf bilingual Libras/Portuguese. The study included 08 bilaterally profound congenital deaf individuals, bilingual Libras/Portuguese, aged between 15 and 25 years old, who were studying or were already completing Elementary School (6th to 9th grade) in the municipality of Tomé-Açu-Pa. The material consisted of two texts in Portuguese: text 01 “O Tatu com Vergonha”, with graphic prosodic marking; and text 02 “O Galo ea Raposa”, without graphic prosody marking. Therefore, 04 participants silently read and answered a questionnaire with 06 multiple choice questions of the text with graphic prosodic marking and 04 performed the same task with the text without the graphic prosodic marking. The results of this research showed that the participants who read the written text of the Portuguese language with the graphic prosodic marking obtained 63% of correct answers. And the participants who read the written text of the Portuguese language without the graphic prosodic marking reached 67% of correct answers. Such evidence allows us to infer that graphic prosodics did not influence the processing of silent reading of written texts in Portuguese written by bilateral Libras/Portuguese bilingual profound congenitally deaf people, contrary to Fodor's (2002) “Implicit Prosody Hypothesis”. Possibly confirm Carvalho's investigations (2016) that deaf people understand written texts in the Portuguese language through semantics.